Bahasa Inggris - Ali Khasan Al Farishi; Binar Kurnia Prahani; Mita Anggaryani; Muhammed Akif Kurtulus (Universitas Negeri Surabaya, 2025)
Objective: Physics learning on sound wave topics, particularly open-pipe organ systems, is often perceived as abstract due to the limited availability of contextual and meaningful learning media. This study aims to develop and evaluate the feasibility of the BASA Booklet (Bamboo Acoustic STEM Approach) as a physics learning medium that integrates the STEM approach, gamification, and ethnophysics through the local wisdom context of bamboo flute instruments. Method: This study employed a Research and Development (R&D) approach using a modified Borg and Gall development model, implemented up to the main field-testing stage. The research subjects consisted of physics teachers and pre-service physics teachers as potential users of the developed media. Data were collected using feasibility questionnaires that assessed media design, learning content, and gamification aspects, and were analyzed descriptively. Results: The results of the main field testing indicate that the BASA Booklet received positive responses across all evaluated aspects, demonstrating that the developed media is conceptually and pedagogically feasible. Respondents perceived the booklet as visually engaging, easy to use, and supportive of independent and structured learning, particularly for abstract physics concepts related to sound waves and open-pipe organ principles. Novelty: The novelty of this study lies in the development of a culture-based, gamified STEM booklet grounded in ethnophysics, which integrates local cultural contexts into physics learning. This model offers an alternative approach to making abstract physics concepts more contextual, meaningful, and relevant. Nevertheless, further studies are required to examine the classroom implementation and effectiveness of the BASA Booklet.